Streptokinase mutations relieving Escherichia coli K-12 (prlA4) of detriments caused by the wild-type skc gene. - Müller, J (1989)
A novel phenotype is described for Escherichia coli K-12 carrying the prlA4 allele determining a membrane component of the protein export mechanism. It is manifest as transformation deficiency for plasmids containing the cloned group C streptococcal streptokinase gene, skc. Streptokinase plasmid mutations relieving the prlA4 strain of this deficiency fell into three classes. Class 1 included skc::IS5 insertions, with IS5 integrated in a region encoding the Skc signal sequence and inactivating skc. Class 2 included IS1 insertions leaving skc intact but reducing skc expression, presumably by altering the function of the skc promoter as judged by an insertion site close to the -35 region. The most interesting class, 3, included skc deletions removing the entire signal sequence or a tetrapeptide from its hydrophobic core. The tetrapeptide deletion reduced the size, hydrophobicity, and predicted alpha-helicity of the central region of the Skc signal sequence but facilitated the export of mature Skc in both the wild type and the prlA4 mutant. These findings indicate that the incompatibility between prlA4 and skc is related to deleterious effects of the Skc signal sequence. The tetrapeptide deletion may function by altering the conformation of the signal sequence so as to render interaction with both the PrlA wild-type protein and the PrlA4 mutant protein less detrimental to the export mechanism. These findings also provide an explanation for the difficulties encountered in cloning streptokinase genes in E. coli plasmids and maintaining their structural stability.